(untitled) (International Journal of Engineering and Computer Science, 2017)
In this paper, we consider the mobile ad hoc network (MANET) which consists of two types of mobile nodes called traditional and relay nodes. The traditional node has limited energy whereas the relay node has relatively abundant energy. The primary objective of this paper is to minimize the power consumption in the mobile ad hoc networks. The main idea behind the proposed relay node deployment framework is to efficiently deploy the relay nodes, so that the traditional nodes can utilize them as intermediate hops for communication. This improves the energy efficiency across the traditional node thereby maximizing the network life time. The proposed framework utilizes the mobility prediction scheme and works in tandem with the underlying MANET routing protocol called Maximum-Residual Energy Routing Protocol (MRERP). Two strategies of the relay deployment problem are presented together with the solutions, to achieve different goals. Strategy 1, termed Min-Total, aims to minimize the total energy consumed across all the traditional nodes during data transmission, while strategy 2, termed Minimum-Maximum, aims to minimize the maximum energy consumed by a traditional node during data transmission. Our solution enables the prioritization of individual nodes in the network based on residual energy profiles. Results indicate that the proposed framework results in significant energy savings, even when the relay nodes constitute a small fraction of the total nodes in the network.